Diskussionspapier für eine Reform der Krankenhausfinanzierung in Deutschland aus der Perspektive der Intensivmedizin - Riessen, Reimer; Markewitz, Andreas; Grigoleit, Maja; Karagiannidis, Christian; Waydhas, Christian; van den Hooven, Thomas; Hermes, Carsten; John, Stefan; Burchardi, Hilmar; Möckel, Martin; Janssens, Uwe; Dennler, Ulf (Medizinische Klinik - Intensivmedizin und Notfallmedizin, 2019)
In Germany, there are currently many voices calling for a reform of hospital planning and reimbursement to correct some aberrations of the last decades and to enable the system to cope with future challenges. Some recent political decisions to change the structures of emergency medical services as well as the introduction of mandatory nurse-to-patient ratios and the exclusion of the cost for nursing from the case-based hospital reimbursement represent first steps of a reform, which also affects intensive care and emergency medicine. In this discussion paper a group of intensivists, emergency physicians, medical controllers, and representatives of nurses suggest more far-reaching changes, which can be summarized in 5 points: (1) General hospitals with intensive care units (ICU) and emergency departments (ED) which are part of the emergency medical system should be considered as an element of public service and be planned accordingly. (2) The planning of the intensive care infrastructure should be based on the three levels of emergency medical services to identify hospitals that are system relevant and to define appropriate criteria for structure and quality measures. (3) Hospital reimbursement should consist of a base amount (covering costs for hospital staff, infrastructure plus investments) and case-based fees (covering material costs). (4) To determine the requirements for nurses, physicians, and other medical staff, adequate tools for ICU and ED should be applied. (5) For these purposes as well as for quality management and optimal medical care, hospitals should be provided with a substantially improved IT-infrastructure.
CRIS-Team Scopus Importer:2019-11-26
Keywords: Diagnosis-related groups; Hospital costs; Hospital planning; Intensive care medicine